Management Strategies of Schools Under The Saint Gabriel’s Foundation of Thailand to Enhance Sustainable Environmental Development - Sakonthawat, Sakda (Scholar: Human Sciences, 2014)
This study was conducted in descriptive research approach. It aimed to study the authentic state and the desirable state, analyze strengths, weaknesses, opportunities and threats and develop management strategies of 15 schools under the Saint Gabriel’s Foundation of Thailand to enhance sustainable environmental development. The participants comprised of the 75 school administrators, 350 teachers, 388 parents, 373 students and 11 experts. The instruments used in this study were the questionnaire and the strategic evaluation form of feasibility and appropriateness. The data were analyzed by frequency, percentage, average, standard deviation, PNI Modifier and content analysis